2018
DOI: 10.1002/2017ja024744
|View full text |Cite
|
Sign up to set email alerts
|

How Often Do Thermally Excited 630.0 nm Emissions Occur in the Polar Ionosphere?

Abstract: This paper studies thermally excited emissions in the polar ionosphere derived from European Incoherent Scatter Svalbard radar measurements from the years 2000–2015. The peak occurrence is found around magnetic noon, where the radar observations show cusp‐like characteristics. The ionospheric, interplanetary magnetic field and solar wind conditions favor dayside magnetic reconnection as the dominant driving process. The thermal emissions occur 10 times more frequently on the dayside than on the nightside, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A description of the ESR is given by Wannberg et al (1997). The handling of the ESR data for the period of interest in this paper is exactly the same way as compared to Kwagala et al (2018) and is described in detail therein and is quickly summarized here. The Naval Research Laboratory Mass Spectrometer and Incoherent Scatter Radar 2000 model (NRLMSISE-00; Picone et al, 2002) has been used to generate the number density of atomic oxygen.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations
“…A description of the ESR is given by Wannberg et al (1997). The handling of the ESR data for the period of interest in this paper is exactly the same way as compared to Kwagala et al (2018) and is described in detail therein and is quickly summarized here. The Naval Research Laboratory Mass Spectrometer and Incoherent Scatter Radar 2000 model (NRLMSISE-00; Picone et al, 2002) has been used to generate the number density of atomic oxygen.…”
Section: Datamentioning
confidence: 99%
“…Earlier literature (e.g., Kozyra et al, ; Lockwood et al, ) reports 3000 K as the electron temperature beyond which thermally excited emissions can become important. Kwagala et al () found an additional population of thermally excited emissions at lower temperatures (∼2300–3000 K) when extreme electron densities (>5 × 10 11 m −3 ) prevailed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An electron temperature greater than about 2300 K is required to thermally excite significant OI 630.0 nm emission (Carlson et al, 2013;Kwagala et al, 2017), which has a much lower excitation threshold (1.96 eV) than the emission observed by ASK. The electron temperature during event 1 was below 2000 K, and therefore, there cannot be any significant thermally excited emission, suggesting the presence of a non-thermal (i.e.…”
Section: Discussion and Theorymentioning
confidence: 97%